Unlocking the potential of pyroptosis in tumor immunotherapy: a new horizon in cancer treatment - Yin, Qinan; Song, Si-Yuan; Bian, Yuan; Wang, Yiping; Deng, Anchen; Lv, Jianzhen; Wang, Yi (Frontiers in Immunology, 2024)
Background: The interaction between pyroptosis-a form of programmed cell death-and tumor immunity represents a burgeoning field of interest. Pyroptosis exhibits a dual role in cancer: it can both promote tumor development and counteract it by activating immune responses that inhibit tumor evasion and encourage cell death. Current tumor immunotherapy strategies, notably CAR-T cell therapy and immune checkpoint inhibitors (ICIs), alongside the potential of certain traditional Chinese medicinal compounds, highlight the intricate relationship between pyroptosis and cancer immunity. As research delves deeper into pyroptosis mechanisms within tumor therapy, its application in enhancing tumor immune responses emerges as a novel research avenue. Purpose: This review aims to elucidate the mechanisms underlying pyroptosis, its impact on tumor biology, and the advancements in tumor immunotherapy research. Methods: A comprehensive literature review was conducted across PubMed, Embase, CNKI, and Wanfang Database from the inception of the study until August 22, 2023.The search employed keywords such as "pyroptosis", "cancer", "tumor", "mechanism", "immunity", "gasdermin", "ICB", "CAR-T", "PD-1", "PD-L1", "herbal medicine", "botanical medicine", "Chinese medicine", "traditional Chinese medicine", "immunotherapy", linked by AND/OR, to capture the latest findings in pyroptosis and tumor immunotherapy.Results: Pyroptosis is governed by a complex mechanism, with the Gasdermin family playing a pivotal role. While promising for tumor immunotherapy application, research into pyroptosis's effect on tumor immunity is still evolving. Notably, certain traditional Chinese medicine ingredients have been identified as potential pyroptosis inducers, meriting further exploration.This review consolidates current knowledge on pyroptosis's role in tumor immunotherapy. It reveals pyroptosis as a beneficial factor in the immunotherapeutic landscape, suggesting that leveraging pyroptosis for developing novel cancer treatment strategies, including those involving traditional Chinese medicine, represents a forward-looking approach in oncology.